Ageism and age discrimination in health care: Fact or fiction? A narrative review of the literature. Issue 4 (August 2015) - Kydd, Angela; Fleming, Anne
Highlights The concept of old age is poorly defined in the literature. Discrimination can be self-assigned. The individual's experience of vulnerability needs to be addressed. Person centred care negates discrimination.